Manajemen Pembelajaran Pendidikan Pancasila Dan Kewarganegaraan Kelas VIII Pada Kurikulum Merdeka Di SMPN 1 Kota Serang - Abdul Malik Assalafi; Alifah Hanan; Berliana Dian Permatasari; Difa Armenia Setiawan; Suci Fikriyah; Ratna Sari Dewi; Lukman Hidayat (Jurnal Kajian dan Penelitian Umum, 2023)
This study describes the implementation of PPKn Curriculum Merdeka learning management in Class VIII of SMP Negeri 1 Serang City. This research applies qualitative descriptive research method. Data was collected by applying observation, interview, and documentation techniques. The results showed that the implementation of PPKn learning management in Class VIII SMP Negeri 1 Kota Bengkulu had fulfilled the principles of implementing PPKn learning management in the independent curriculum, including the stages of planning, implementing learning, and evaluating learning outcomes. The principal, vice principal, PPKn teachers, and students have understood the vision, mission, and objectives of PPKn subjects.